Evaluation of the effects of repeated disinfection on medical exam gloves: Part 1. Changes in physical integrity. Issue 2 (9th February 2022) - Shless, Jared S.; Crider, Yoshika S.; Pitchik, Helen O.; Qazi, Alliya S.; Styczynski, Ashley; LeMesurier, Roger; Haik, Daniel; Kwong, Laura H.; LeBoa, Christopher; Bhattacharya, Arnab; Hamidi, Youssef K.; Phalen, Robert N.
Abstract: COVID-19 has created shortages of personal protective equipment. In resource-constrained situations, limited cycles of disinfection and extended use of gloves is recommended by the U.S. Centers for Disease Control and Prevention to conserve supplies. However, these guidelines are based on limited evidence. In this study, serial cycles of hand hygiene were performed on gloved hands using an ethanol-based hand rub (six and 10 cycles), 0.1% sodium hypochlorite (bleach) solution (10 cycles), or soap and water (10 cycles) on latex and nitrile medical exam gloves from the United States and India. A modified water-leak test evaluated glove integrity after repeated applications of these disinfecting agents. When aggregated, dilute bleach demonstrated the lowest difference between treatment and control arms: −2.5 percentage points (95% CI: −5.3 to 0.3) for nitrile, 0.6 percentage points (95% CI: −2.6 to 3.8) for non-powdered latex. For U.S.-purchased gloves tested with six and 10 applications of ethanol-based hand rub, the mean difference in failure risk between treatment and control gloves was within the prespecified non-inferiority margin of five percentage points or less, though some findings were inconclusive since outside the margin. The aggregated difference in failure risk between treatment and control was 3.5 percentage points (0.6 to 6.4) for soap and water, and 2.3 percentage points (−0.5 to 5.0) and 5.0 percentage points (1.8 to 8.2) for 10 and 6 applications of ethanol-based hand rub, respectively. Most leaks occurred in the interdigital webs (35%) and on the fingers (34%). This indicates that some combinations of glove types and disinfection methods may allow for extended use. Ten applications of dilute bleach solution had the least impact on glove integrity. However, the majority of glove and exposure combinations were inconclusive. Additional testing of specific glove and disinfectant combinations may inform future strategies to guide extended use during glove shortages. Additional considerations, not evaluated here, include duration of use, disinfectant chemical permeation, and the effects of hand temperature, movement, and manipulation of instruments on glove integrity.